Fixed Points of Hyperbolic Contraction Mappings on Hyperbolic Valued Metric Spaces - Sager, Nilay; Sağır, Birsen (Sarajevo Journal of Mathematics, 2022)
In this paper, we give some elementary topological concepts and results on hyperbolic valued metric space and then, we introduce two fixed point theorems for hyperbolic valued metric spaces by defining hyperbolic contraction mapping. We also give an example which support the main result.